Are shocks to wood fuel production permanent? Evidence from the EU - Jaunky, Vishal; Lundmark, R. (2015)
© 2015 by the authors.This paper investigates whether shocks (economic effects) to wood fuel production for 18 countries of the European Union (EU) over the period 1961-2012 are temporary or persistent. A variety of time-series and panel data unit root tests are employed. The presence of structural breaks is taken into account when performing those tests. Wood production in approximately 78% of the countries is found to follow a non-stationary process supported by the result that most of the panel unit root tests also point towards a non-stationary process. This indicates that the economic effect will tend to be persistent and suggests that policies affecting wood fuel production, implicitly or explicitly, will have enduring effects. For instance, forest conservation policies will persistently reduce the wood fuel production level.